2014
DOI: 10.1016/j.cmet.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A Redox-Dependent Mechanism for Regulation of AMPK Activation by Thioredoxin1 during Energy Starvation

Abstract: Summary 5'-AMP-activated protein kinase (AMPK) is a key regulator of metabolism and survival during energy stress. Dysregulation of AMPK is strongly associated with oxidative stress-related disease. However, whether and how AMPK is regulated by intracellular redox status remains unknown. Here we show that the activity of AMPK is negatively regulated by oxidation of Cys130 and Cys174 in its a subunit, which interferes with the interaction between AMPK and AMPK kinases (AMPKK). Reduction of Cys130/Cys174 is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
211
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(219 citation statements)
references
References 32 publications
6
211
1
1
Order By: Relevance
“…Our studies confirmed the findings of Shao et al 25 that striated muscles, especially the heart muscle, may accelerate glucose uptake under ischemic conditions. Mechanism of this process is based on the thioredoxin1-mediated activation of Prka-dependent translocation of glucose transporters into a cell membrane.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…Our studies confirmed the findings of Shao et al 25 that striated muscles, especially the heart muscle, may accelerate glucose uptake under ischemic conditions. Mechanism of this process is based on the thioredoxin1-mediated activation of Prka-dependent translocation of glucose transporters into a cell membrane.…”
Section: Resultssupporting
confidence: 95%
“…Such redox-associated mode of glucose uptake stimulation may be critical for cardiac protection against ischemia and is in agreement with the findings of Shao et al 25 showing that heart muscle may accelerate glucose uptake in metabolic stress conditions.…”
supporting
confidence: 78%
“…36 Recent studies have indicated that the AMPK activity can be regulated by redox modification under oxidative stress. 20 In this study, we found that AMPK was activated by HBVinduced oxidative stress, indicating that virus-induced ROS accumulation could exert a feedback regulation on metabolic stress. TXN, an important reducing enzyme that catalyzes disulfide reduction, serves as a vital cofactor for AMPK activation by preventing the oxidative aggregation of AMPK.…”
Section: Discussionmentioning
confidence: 94%
“…20 As shown in Figure S5A, H 2 O 2 or diamide (a thiol oxidizing compound) induced a mobility shift of PRKAA in HepG2 cells, which could be reversed by dithiothreitol, a reducing agent that breaks disulfide bonds. However, there was no significant mobility shift of PRKAA in response to HBV-induced oxidative stress (Fig.…”
Section: Prkaa/ampk Is Activated By Hbv-induced Ros Accumulationmentioning
confidence: 97%
“…Activation of AMPK in the liver also represses expression of gluconeogenesis enzymes such as Pck1 and G6pc 40 , results opposite from those observed in heme oxygenase-depleted hepatocytes. If the increases in Pck1 and G6pc transcript levels in HO-depleted hepatocytes were due to decreased AMPK activity (perhaps mediated by increased oxidative stress 41 ), transcript levels of genes involved in other anabolic pathways would also be expected to be elevated 42 . However, this was not the case: the expression of key genes involved in lipogenesis, such as sterol regulatory element-binding protein-1, carbohydrate response element-binding protein, acetyl CoA carboxylase, fatty acid synthase, stearoyl-CoA desaturase, and glycerol-3-phosphate acyltransferase, was essentially unaltered.…”
Section: Discussionmentioning
confidence: 99%